Kualitas Pelayanan Sertifikat Tanah Hak Milik di Kantor Pertanahan Kabupaten Jayapura: The Service Quality of Certificate Land Title in The Land Office of Jayapura Regency - Sapioper, Hiskia C.M.; Flassy, Marlina; ilham, Ilham (Jurnal Borneo Administrator, 2021)
The study aims to know and describe the quality of services and arrangements in the land certificates processing at Land Office of Jayapura Regency, Papua Province in Indonesia. This was a qualitative research by using service quality theory. This theory consists of five main dimensions namely, tangible, empathy, reliability, responsiveness, and assurance. The primary data was obtained through observation and interviews, while secondary data was obtained through library research. Data analysis was carried out through reduction and presentation, conclusions, and verification. Therefore, the results showed that service procedures were implemented according to standards, and the officers' competence were considered adequate. However, in terms of facilities and infrastructure, service standards did not meet the required expectations. Finally, the duration of the process indicated that the services provided were not responsive to the community needs. Kajian ini dilakukan untuk mengetahui dan mendeskripsikan kualitas pelayanan dan pengaturan pertanahan dalam pengurusan sertifikat tanah hak milik di Kantor Pertanahan Kabupaten Jayapura, Provinsi Papua. Jenis penelitian ini adalah kualitatif dengan menuang teori kualitas pelayanan yang terdiri atas lima dimensi pokok: tangible, empathy, reliability, responsiveness, assurance. Data primer diperoleh melalui pengamatan dan wawancara, data sekunder berasal dari studi kepustakaan. Analisis data dilakukan melalui reduksi data, penyajian data, penarikan kesimpulan dan verifikasi. Hasil penelitian ini menunjukkan bahwa prosedur pelayanan telah dilaksanakan sesuai standar pelayanan, serta kompetensi petugas juga dinilai telah memadai. Kendati demikian, dari segi sarana dan prasarana belum sepenuhnya sesuai dengan standar pelayanan, lamanya proses penyelesaian pengaduan juga mengindikasikan bahwa pelayanan yang diberikan kurang memuaskan kebutuhan masyarakat selaku pengguna layanan.